Exogenous MeJA modulates postharvest tomato aroma by suppressing JAs-ethylene signaling crosstalk - Li, Xuehui; Tan, Xiaoyu; Gao, Yubang; Luo, Xinyu; Xu, Dongguang; Wang, Yiting; Geng, Xinli; Yang, Xiaolin; Xie, Yuhua; Niu, Qiuhong; Ren, Xiaopu; Wang, Libin (Frontiers in Plant Science, 2025)
BackgroundUntil recently, the mechanism underlying methyl jasmonate (MeJA)-mediated suppression of ethylene metabolism and its impact on quality formation in ripening tomatoes has not been fully clarified. This study aimed to investigate how exogenous MeJA application at the breaker stage affects endogenous jasmonates (JAs), ethylene production, metabolic pathways, and flavor profiles in 'FL 47' tomatoes.MethodsExogenous MeJA was applied to red 'FL 47' tomatoes at the breaker stage. We measured endogenous JAs (especially JA-Ile), ethylene production, enzyme activities (LOX, AOC, AOS, OPR, ACO, ACS), mRNA abundances of related genes (SlLOXD, SlAOC, SlAOS, SlOPR3, SlACO1, SlACS2, SlACS4, SlMYC2, SlMED25, SlETR3, SlETR4, SlETR7, SlEIN2, SlEIL1, SlEBF1, SlEBF2, SlERF1, SlLOXC, SlPSY1, SlCCD1A, SlCCD1B, SlBCAT1), production of sugars, organic acids, and 21 volatiles, as well as substrate contents (phytoene, phytofluene, trans-lycopene, γ-carotenoid, β-carotenoid, linoleic and linolenic acid) in MeJA-treated and control fruits.ResultsMeJA treatment suppressed endogenous JAs (JA-Ile by 13%) and ethylene production by 33%. Enzyme activities in metabolic pathways were reduced to over 87% of control levels, and mRNA abundances of the aforementioned genes decreased by 17-30%. Production of sugars, organic acids, and volatiles was altered, leading to changes in flavor profile. Specifically, six key ethylene-regulated volatiles (geranyl acetone, 1-penten-3-one, 6-methyl-5-hepten-2-one, 2-methyl butanal, 3-methyl butanal, 3-methyl butanol) were reduced, concomitant with 19-29% lower mRNA abundances of biosynthetic genes (SlLOXC, SlPSY1, SlCCD1A, SlCCD1B, SlBCAT1) and substrate contents over 74% of control levels.DiscussionBy considering the positive relationship between endogenous JA-Ile and ethylene levels in ripening fruit, our results imply that MeJA-mediated changes in aroma profile in red 'FL 47' tomatoes may result from mitigated endogenous JAs (especially JA-Ile) and ethylene biosynthesis and signaling transduction processes. These findings enhance understanding of hormone interactions in fruit quality formation and suggest potential applications for improving post-harvest tomato flavor.